Large-scale construction programme resilience against creeping disruptions: Towards inter-project coordination - Shen, Wenxin; Ying, Wenchi (International journal of project management, 2022)
•This study examines programme resilience against creeping disruptions through inter-project coordination.•Creeping disruptions that influence programme resilience at interdependent boundaries amongst component projects are highlighted.•Roles, objects and process impacting programme resilience are identified.•A three-phase process model comprising roles, objects, mechanisms and actions is further identified as an integrated framework. Extant resilience research in project management focused mainly on the project level and sudden disruptions. However, resilience at the programme level, especially resilience against creeping disruptions, remains unexplored. This study adopts boundary object theory as the theoretical lens to explore programme resilience against creeping disruptions. Based on the case study of a large-scale construction programme Expo 2020 Dubai, a process model is proposed to unveil how programme resilience can be fostered through inter-project coordination. The model includes roles (i.e., program coordinators and project managers) and processes (i.e., preparation, mobilisation and response phases) that impact the resilience of the programme. The three-phase resilience process further corresponds to three boundary object-based coordination mechanisms: pull, match, and push, respectively. This study not only contributes to the project/programme resilience and management literatures, but also advances knowledge on resilience.